Investigating discretionary management decision on accounting policy and government monitoring mechanism of non-bearer plant: the case of a stateowned logging company in Indonesia / Widya Perwitasari - Perwitasari, Widya (2024)
The Global Risk Report 2023 reveals that the domination in global risks shifts from economic risks towards environmental risk. Indonesia is exposed to significant environmental risk partly due to its natural landscape. Indonesia has great concern in promoting a sustainable environment demonstrated by actively participating in global initiatives. Statistics indicates that Indonesia is exposed to significant forest resource exploitation and forest crimes. The Corruption Eradication Commission (CEC) in 2015 uncovered a significant amount of timber production is unreported due to allegedly illegal logging activities, indicating a significant amount of government revenue loss. Previous studies suggested that accounting is valuable in addressing forest crimes by promoting transparency, accuracy, and accountability in financial transactions related to forestry activities. However, previous studies show inconsistent accounting policies by forestry companies, which can lead to a lack of standardized reporting and comparability. The CEC in 2015 uncovered that monitoring and enforcement of regulations and financial reporting standards for logging companies are inadequate due to insufficient resources, corruption, or weak governance. This may lead to unreliable financial performance reporting. There is limited research on the application and the challenges of Indonesian FRS 69: Agriculture. Furthermore, limited research shows the role of financial reporting in government monitoring mechanisms. Therefore, further research is required to examine the implementation and the challenges of the Indonesian FRS 69: Agriculture, and the government monitoring mechanism in evaluating the financial performance of logging companies. The research attempts to present evidence in the current practice and the challenges of accounting for non-bearer plants, and the government monitoring mechanism related to financial performance evaluation. The research adopts qualitative methodology and acquires primary data from interviews with accounting officers of logging companies, external auditors, case company officers, and government officers. The research acquires secondary data from the professional guidelines, existing government regulations, and other various documents. Therefore, the findings of the research are a mix of the present professional guidelines and regulations, present practices, respective roles, and perceptions pertaining to the issues in the measurement, valuation, and reporting of non-bearer plants in Indonesia. Based on the research findings, it is concluded that five factors may have contributed to the deficiency in Indonesia forest management. First, awareness, capability, and enforcement of the government. Second, capability and compliance of the logging companies. Third, awareness and capability of investors. Fourth, the lack of guidance. Fifth, the lack of benchmarking practices. The research provides practical recommendations for the identified problems normatively. The research contributes to the theory by presenting a comprehensive study incorporating different perspectives from people representing important group of interests. The research contributes to the methodology by presenting rich information and evidence on the current practice and challenges encountered by logging companies in Indonesia. The research contributes to the practice by presenting current practice as a benchmark for logging companies while at the same time providing recommendations for improvements to the policy maker and financial reporting standard setting body in Indonesia.